Makna dan Filosofi Silat Perisai dalam Penyambutan Tamu Adat Melayu Riau - Septina Azzahwa; Risna Wulandari; Hikmah Kamilah; Fauziah Yenika Putri; Arwiwa Shofi Zetdafi; Pandu Wijaya; Dinda Lorenza Pratiwi; Elmustian Elmustian (BADAN PENERBIT STIEPARI PRESS, 2025)
Using the example of Lontiok's house on Belimbing Island, this article discusses the philosophy and meaning of